A tomographic microscopy-compatible Langendorff system for the dynamic structural characterization of the cardiac cycle - Dejea, Hector; Schlepütz, Christian M.; Méndez-Carmona, Natalia; Arnold, Maria; Garcia-Canadilla, Patricia; Longnus, Sarah L.; Stampanoni, Marco; Bijnens, Bart; Bonnin, Anne (Frontiers in Cardiovascular Medicine, 2022)
Introduction Cardiac architecture has been extensively investigated ex vivo using a broad spectrum of imaging techniques. Nevertheless, the heart is a dynamic system and the structural mechanisms governing the cardiac cycle can only be unveiled when investigating it as such. Methods This work presents the customization of an isolated, perfused heart system compatible with synchrotron-based X-ray phase contrast imaging (X-PCI). Results Thanks to the capabilities of the developed setup, it was possible to visualize a beating isolated, perfused rat heart for the very first time in 4D at an unprecedented 2.75 μm pixel size (10.6 μm spatial resolution), and 1 ms temporal resolution. Discussion The customized setup allows high-spatial resolution studies of heart architecture along the cardiac cycle and has thus the potential to serve as a tool for the characterization of the structural dynamics of the heart, including the effects of drugs and other substances able to modify the cardiac cycle.